Agrypnia excitata and obstructive apnea in a patient with fatal familial insomnia from China: A case report - Sun, Congcong (Medicine (Baltimore), 2017)
RATIONALE: Fatal familial insomnia (FFI) linked to a D178N/129M haplotype mutation in the PRNP gene is the most common genetic prion disease in the Han Chinese population. Here, we describe a Han Chinese patient with FFI who exhibited agrypnia excitata and obstructive apnea. PATIENT CONCERNS: A 46-year-old man displayed involuntary movements during sleep time, snoring, autonomic nervous system dysfunction, cognitive deficit, brainstem symptoms, myoclonus and ataxia in order within 8 months. The electroencephalogram (EEG) and Magnetic Resonance Imaging (MRI) revealed abnormal changes but without the typical prion disease signs. DIAGNOSES: After the conduction of Polysomnogram (PSG) and gene detection of PRNP, the patient was diagnosed as FFI. Three others exhibiting the same clinical manifestations were observed in the large family. INTERVENTIONS: The patient responded temporally well to drugs that strengthening the function of mitochondria. OUTCOMES: Sudden death occurred after 3 month ever since the diagnoses. The total disease course was 11 months. LESSONS: The insomnia in FFI is complex, agrypnia excitata and obstructive apnea can also be indicators for FFI. Polysomnogram is necessary for recognizing the sleep loss when the symptom of insomia is not typical. Improving energy metabolism may be a potential treatment for it.